PERAN MARKETPLACE DALAM MENINGKATKAN AKSES PEMASARAN UMKM DI INDONESIA - Manurung, Maya; juliana putri, Juliana Putri (Program Studi Ekonomi Syariah, 2024)
This study aims to examine the role of marketplaces in improving marketing access for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Digital marketplaces have become a crucial channel for MSMEs to expand their market reach and enhance competitiveness amid increasing competition. This research employs a qualitative approach using a literature review method, which involves collecting and studying existing literature from various sources such as journals, articles, websites, and other relevant references. The findings indicate that marketplaces not only facilitate the marketing process but also enhance the visibility of MSME products, expand access to broader markets, and provide access to technologies that support business management. Additionally, this study identifies the challenges faced by MSMEs in utilizing digital platforms, such as limited resources, difficulties in adapting to technology, and intense price competition. Nevertheless, the benefits derived from using marketplaces in MSME marketing are proven to be significant, both in terms of increased sales and business network development. This study is expected to provide insights for MSME actors and digital platforms to optimize marketing potential through marketplaces.